The role of iron oxidizing bacteria to the quality of leachate on acid sulphate soil - Khairatun Napisah; Azwar Maas; Sri Nuryani Hidayah Utami; Wahida Annisa Yusuf (Jurnal Ilmu Pertanian, 2020)
The problem encountered in acid sulphate soil is the presence of pyrite (FeS2) which causes soil  to have highly acid reaction when the pyrite is oxidized. The decline in quality not only occurs on the soil  but also on the quality of the surrounding waters. One way to improve the quality of the leachate is by draining it through biofilter plants in the form of purun tikus (Eleocharis dulcis) and bulu babi (Eleocharis retroflaxa) which can absorb or neutralize these elements. The purpose of this research was to know the inoculant influence of iron oxidizing bacteria to leachate quality in acid sulphate soil. The research was conducted on a pot scale in greenhouse. The research was in randomized block design (RBD) of 3-factors with 3 replications. The first factor was inoculants, the second factor was water management, and the third one was phytoremediation material (Eleocharis dulcis  and Eleocharis retroflaxa). The results showed that the plant height in the inoculant treatment+wood charcoal was in the range of 89.33−95.33 cm, while that in the inoculant treatment+husk charcoal was in the range of 89.50−93.00 cm. Meanwhile, the yield of rice with bacteria oxidizing iron inoculant+wood charcoal was higher, which was at 6.77 ton.ha-1 than inoculant treatment of oxidizing iron+husk charcoal which was only 5.95 ton.ha-1.